Tributação e bem comum - Pereira, Állirson Oliveira Fortes (2021)
Theory of Natural Law, Economic Analysis of Law and the Tax Incidence Matrix Rule and how this illuminates the relationship between taxation and the common good. Therefore, it aims to demonstrate that the Economic Analysis of Law and the Incidence Matrix Rule are not only compatible with the Neoclassical Theory of Natural Law by John Finnis, but also as precious instruments for the authority to make the search for the common good effective. Having the realist tradition as an epistemic foundation, and using the dialectical method, and the hypothetical-deductive method, with the bibliographic review tool. The work is divided into 4 chapters: Natural Rights, Economic Analysis of Law and Incidence Matrix Rule. In the first 3 chapters a new layer will be inserted so that in the fourth chapter, the answer about the possibility of conciliation is the conclusion. Starting from the very first architectural principle of Practical Reason, good must be sought and evil must be avoided and the first substantial principles (life, knowledge, game, friendship, marriage, religion and practical reasonableness), going to the supreme principle of morality ( love your neighbor as yourself) and the golden rule (do to others what you want them to do to you) where the requirements of practical reasonableness result in the morality of human action, reaching human flourishing, where each person must seek the goods human beings in a reasonable manner and the pursuit of each human person within the requirements of practical reasonableness. Common Good, such is the flowering of each person in the political community, being the substantive purpose of authority. The Economic Analysis of Law complements the criteria of justice as requirements of the common good, allowing the authority in the legislative or hermeneutical task to have before it the design of the structure of incentives that gives greater effectiveness to that intended objective, under the requirements of practical reasonableness, that is, a taxation that not only generates resources for the authority to pay for those goods that can only be achieved in a community way or even encourage/induce behaviors. The Incidence Matrix Rule, as a logical-semantic structure, gives the authority a greater degree of security and reduces the discretion of the judge. Thus, it is clear that a reconciliation between the Neoclassical Theory of Natural Law, the Economic Analysis of Law and the Incidence Matrix Rule is not only possible, but also desirable.